Proposal for Urban Subcenters identification based on the Spatial Distribution Of Functions: Case of Maputo City - Mozambique - Chicombo, Tomé Francisco (Sociedade & Natureza, 2021)
This study presents a methodological proposal for identification of new urban functional centralities based on data from the points of interest of Open Street Map platform. On the other hand, data collected through fieldwork interviews were also used for the study and complemented with Google Earth imagery. Points of interest data were classified according to pre-defined criteria representing urban features. Each criterion was assigned a weight. The criteria weights were calculated based on the Analytical Hierarchical Process (AHP) method. For this purpose, interviews were carried out with specialists and individuals with greater experience of living in the study area, based on their perception regarding to the distribution of urban functionalities. The results of interviews were introduced in matrices that allowed the calculation of weights for each criterion. In addition, points of interest data were edited and processed through ArcGis application, in which a map was produced showing the spatial distribution of the points of interest and the respective levels of centrality. Therefore, it was possible to identify from this study some points of concentration outside the historic center of the Maputo city, which show evidence of emergence of new functional centralities as a result of implementation of new urban infrastructure in the non-central area, mainly related to commerce and services provision.